Physical Modelling of Rainfall-Induced Sandy and Clay-Like Slope Failures - Martina Vivoda Prodan; Josip Peranić; Sara Pajalić; Željko Arbanas (Advances in Materials Science and Engineering)
Small-scale slope modelling was performed to evaluate the failure process of a landslide triggered by artificial rainfall. The model platform 2.3 m long, 1.0 m wide, and 0.5 m deep was used to build small-scale slope models with the same geometric conditions but different soil types/materials, including sand and two sand-kaolin mixtures with the same slope angle. The hydraulic response of the slope models under simulated rainfall conditions was monitored using volumetric water content, pore water pressure, and matric suction sensors installed at different depths and along different profiles. Slope surface deformation and failure development was also monitored. This paper discusses the factors affecting landslide initiation and propagation, and their relationship to the slope material, infiltration process, and overall soil resistance in a slope related to soil strength, effective stress, and matric suction contribution in the unsaturated part of the slope. Rainfall infiltration caused increase of volumetric water content, dissipation of suction in initially partially saturated materials of the small-scale slope models, resulting in a decrease in effective stresses and shear strength, which in turn led to the occurrence of movements and initiation of slope failures. The main observations arising from the results of the conducted tests relate to initiation and development of the observed instabilities of sandy and clay-like slopes. The test results have shown that within the slopes built from clean sand failure occurs due to groundwater level rising at the slope foot and further retrogressive failure towards the top of the slope, while in the slopes built from sand-kaolin mixtures, instabilities occur in the form of cracks in unsaturated conditions and are the result of matric suction dissipation due to rainfall infiltration.